Importance of vitamin D in the mother and infant in pediatric follow-up (Annals of Medical Research, 2021)
Aim: Vitamin D is a steroid structured the hormone that regulates the calcium and phosphor metabolism in the body and is required for healthy growth, development, and skeletal structure. Apart from its negative effect on bone structure, vitamin D deficiency may form the basis of many diseases. For infants aged between 0-24 months coming to the hospital for regular follow-up, the objective of this study was to evaluate their retrospective serum 25-hydroxyvitamin D levels, maternal vitamin D usage history and their distributions based on gender, age and seasons.Materia and Methods: 992 infants who were admitted to the well-child polyclinic in a training and research hospital in Ankara between January 2018 and May 2019 and detected to have serum 25-hydroxyvitamin D levels below normal were included in our study. The patients were separated into four groups according to their chronological ages with a difference of six months between each group and into three groups based on their vitamin D levels. Groups were also formed according to genders and seasons.Results: Three groups were formed based on serum 25-hydroxyvitamin D values of the infants; values of those below 10.00 ng/mL were classified as the deficiency, those between 10.01-20.00 ng/mL were classified as insufficiency and those between 20.01 and 30.00 ng/mL were classified as an indefinite group. Among 992 infants included in the study, 38 (3.8%) were defined as a deficiency, 380 (38.3%) as insufficiency and 574 (57.9%) as an indefinite group. Lowest 25-hydroxyvitamin D values of the infants were observed in spring and the group aged between 0-6 months.Conclusion: Vitamin D values were detected significantly low in infants under the age of two and especially in those who are in their first six months. This condition requires the regular follow-up of vitamin D levels of the mothers during pregnancy and adequate and careful use of vitamin D prepares support.
Keywords: Child health monitoring; infant vitamin D level; maternal vitamin D level